Medieval artes praedicandi : a synthesis of scholastic sermon structure - Wenzel, Siegfried, 1928- (Medieval Academy books ;, 2015)
In late medieval times theologians and preachers in Western Europe adopted a distinct and rigidly structured sermon format. The scholastic sermon was taught through technical treatises known as artes praedicandi. Wenzel focuses on the main features of the sermon. This book also includes a list of forty-two major surviving artes praedicandi, discussing the evolution of the genre. --Book jacket.